Does Doxycycline Benefit Intensified Hygiene Measures in Patients with Filarial Lymphedema? A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Asia Batool; Makhzan Ali Akbar; Fakhar E. Mahin; Muhammad Sharjeel Abbas; Muhammad Huzaifa Khattak; Bilal Wazir Khan; Meer Murtaza; Nayab Magsi; Tayyaba Ikram Kazi; Muhammad Maaz Amjad; Humaira Bibi; Zohaa Fazal; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Lymphatic filariasis is a vector-borne infectious disease, most commonly caused by Wuchereria bancrofti , that affects 120 million people. It invades the lymphatic system of humans, who are the definitive hosts. We compared the administration of doxycycline with intensified hygiene measures alone in patients diagnosed with bancroftian filariasis. We searched PubMed, Scopus, and Embase and included 12 randomized controlled trials. A random-effects model was used to calculate the mean difference (MD)/risk ratio (RR) and I 2 for heterogeneity. The risk of bias and GRADE evaluated the certainty of evidence. Pooled analysis showed a significant reduction in the number of Wolbachia per microfilaria (MD = −3.09; 95% CI: −3.94 to −2.25; P